Association of Genetic Ancestry With Terminal Duct Lobular Unit Involution Among Healthy Women. (25th March 2022) - Sung, Hyuna; Koka, Hela; Marino, Natascia; Pfeiffer, Ruth M; Cora, Renata; Figueroa, Jonine D; Sherman, Mark E; Gierach, Gretchen L; Yang, Xiaohong R
Abstract: Reduced age-related terminal duct lobular unit (TDLU) involution has been linked to increased breast cancer risk and triple-negative breast cancer. Associations of TDLU involution levels with race and ethnicity remain incompletely explored. Herein, we examined the association between genetic ancestry and TDLU involution in normal breast tissue donated by 2014 healthy women in the United States. Women of African ancestry were more likely than European women to have increased TDLU counts (odds ratio [OR]trend = 1.36, 95% confidence interval [CI] = 1.07 to 1.74), acini counts per TDLU (OR = 1.47, 95% CI = 1.06 to 2.03), and median TDLU span (ORtrend = 1.44, 95% CI = 1.08 to 1.91), indicating lower involution, whereas East Asian descendants were associated with decreased TDLU counts (ORtrend = 0.52, 95% CI = 0.35 to 0.78) after controlling for potential confounders. These associations are consistent with the racial variations in incidence rates of triple-negative breast cancer in the United States and suggest opportunities for future work examining whether TDLU involution may mediate the racial differences in subtype-specific breast cancer risk.